The Strengths and Weaknesses of Artificial Intelligence in Improving Writing Skills: A Users’ Perspective - Jamilah; Wahdaniah; Putri, Yetty Tri; Ginting, Sridinanta Br (STMIK Indonesia Banda Aceh, 2025)
The advancement of artificial intelligence (AI) technology has significantly impacted the education sector, particularly in the development of Indonesian Language writing skills. This study aims to explore how users utilize AI to enhance their Indonesian Language writing skills and to examine their feelings and experiences when using this technology. The study investigated 52 high school students from four schools in Lhokseumawe, Indonesia, who are familiar with using AI in their studies, including writing. This study explores Indonesian high school students' perception and use of AI for writing skills improvement, highlighting benefits and challenges, and the need for guided AI integration in education. A qualitative approach was employed, with data collected through non-participatory online observation, semi-structured interviews, and digital content analysis. The results of the study show that AI helps users improve their grammar, expand their vocabulary, and write more structured texts. However, several limitations were identified, including dependence on the system and a lack of guidance for independent critical thinking. These findings suggest that AI has the potential to be an effective tool for learning to write, but its use still needs to be guided by instructions so as not to reduce the active learning process.